THE EFFECT OF SELF ESTEEM TOWARDS CONSUMPTIVE BEHAVIOUR IN X UNIVERSITY STUDENTS - Dhea Prastika Setiono; Retno Dwiyanti (Psycho Idea, 2020)
s study aims to examine the effect of self esteem on consumptive behavior in X University students. The method in this study uses a quantitative approach. The subjects of this study were 50 University X students. Data were collected using a self esteem scale instrument and a scale of consumptive behavior with a validity test using the product moment correlation technique, while the reliability test was using an alpha cronbrach technique. The self esteem scale has a reliability score of 0.960 while the consumer behavior scale has a reliability score of 0.891. Based on the results of data analysis that has been done, the results show that: there is an influence of self esteem with consumptive behavior in University X students. It is proven that the R. count value is greater than the R. table that is 0.296> 0.284 and the value of P = 0.000 (P <0.05 ).